A quest for useful knowledge: the early development of agricultural accounting in Denmark and Northern Germany. (2nd January 2017) - Lampe, Markus; Sharp, Paul
ABSTRACT: We discuss the early development of sophisticated agricultural accounting in Northern Germany and Denmark within a framework that establishes the role of accounting for knowledge generation and subsequent economic growth. We highlight the work of Thaer, on encouraging and systematising the use of double-entry bookkeeping in agriculture for scientific and efficiency purposes, and that of Gyllembourg, who emphasised the calculation of economic returns in monetary value. Evidence exists to suggest that their work was the basis upon which further developments in accounting practice in the nineteenth century were laid, supporting the rapid modernisation and success of Danish agriculture.